Pengaruh Independensi, Keahlian Dan Pengalaman Audit Terhadap Kemampuan Auditor Mendeteksi Kecurangan Pada Kantor Akuntansi Publik Semarang - Hani Krisnawati; Aniqotunnafiah Aniqotunnafiah; Sella Ria Fitriana (STIKes Ibnu Sina Ajibarang, 2023)
This research aims to determine the influence of independence, audit expertise and experience on the auditor's ability to detect fraud. The population in this research is all auditors who work at the Semarang Public Accounting Firm. There were 85 auditors in the sample in this study. The sample selection method uses a purposive sampling method, while the analysis method used in this research is the multiple linear regression analysis method and is processed using the SPSS version 24 program application. The research results show that independence has no effect on the auditor's ability to detect fraud. However, audit expertise and experience have a positive and significant effect on the auditor's ability to detect fraud.